THE IMPLEMENTATION OF LEARNING CYCLE MODEL IN ENERGY TOPIC AT SENIOR HIGH SCHOOL 2 LAMONGAN - HABIBATUL HUSNA, ANDIKA; SUNARTI, TITIN (Inovasi Pendidikan Fisika, 2018)
THE IMPLEMENTATION OF LEARNING CYCLE MODEL IN ENERGY TOPIC AT SENIOR HIGH SCHOOL 2 LAMONGANAndika Habibatul Husna, Dra. Titin Sunarti, M.SiPhysics Department, Faculty of Mathematics and Natural Science, The Surabaya State UniversityEmail: andikahabibatulh@gmail.com Abstract Based on Law Number 20 Year 2003 on National Education System 1 point 1 explains that the ideal learning in Indonesia should be able to make the students play an active role in the process of improving human quality. One model that can be applied to meet these demands is the learning cycle model (LC). The LC model was first popularized by Robert Karplus. Based on Bybee and colleagues in 1996 in the Sciense Curriculum Improvement Study (SCIS), LC is one of the learning models using constructivism approach. LC consists of 5 syntaxes, namely: (i) engagement, (ii) exploration, explanation, elaboration and evaluation. The purpose of this research is to describe the implementation of LC model in Energy material in SMAN 2 Lamongan. The type of this research is experimental research. The object of this research is determined by using random sampling technique and the research instrument used is the learning activity sheet. The implementation of the LC model is observed by the observer by scoring on the instructional learning sheet and evidenced by the video recording when the learning takes place. The result of this research is almost all the components in the observation sheet of learning implementation. The implementation of learning with LC learning cycle model is very good (LC syntax implemented) at the first meeting and second meeting. The implementation of syntax is shown by the high performance value at the first meeting, which is 88.96% and the second meeting is 89.65%. The results of video analysis also support the performance values ??provided by the observer. Keywords: Learning cycle, learning activities, implementation